Songs of the Ketu cult of Bahia, Brazil - Merriam, Alan P. (International Library of African Music, 1956)
The present study is directed toward establishing the music structure of an African- derived cult group of Bahia, Brazil. Such work is at present of considerable importance to the entire study of the musical relationships between New World and African Negro cultures; to date very few studies have been made. Before ethnomusicology can begin to make its most significant contributions to the study of the New World Negro acculturative problems and the broader questions of cultural dynamics that derive from it, a series of such works as that being undertaken here must be completed, so that factual information will become available for comparative data.
Keywords: African Music